2019
DOI: 10.3390/antiox8100493
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Antioxidant Activities of Polysaccharides Isolated from Celluclast-Assisted Extract of an Edible Brown Seaweed, Sargassum fulvellum

Abstract: It has been reported that enzymatic digestion of algae could improve the yield and enhance the biological activity compared to water and organic extraction. Our previous research indicated that Celluclast-assisted extract of Sargassum fulvellum (SF) possessed higher carbohydrate content and stronger antioxidant activity compared to water and other enzyme-assisted extracts. In the present study, we evaluated the antioxidant activities of polysaccharides from SF (SFPS) in vitro in Vero cells and in vivo in zebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 47 publications
3
34
0
Order By: Relevance
“…Wang et al (2019) isolated sulfated polysaccharides from the edible seaweed Sargassum fulvellum (SFPS) and investigated the effect of SFPS on AAPH-induced oxidative stress. The results indicated that SFPS effectively suppressed AAPH-induced oxidative stress in vitro in Vero cells and in vivo in zebrafish [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al (2019) isolated sulfated polysaccharides from the edible seaweed Sargassum fulvellum (SFPS) and investigated the effect of SFPS on AAPH-induced oxidative stress. The results indicated that SFPS effectively suppressed AAPH-induced oxidative stress in vitro in Vero cells and in vivo in zebrafish [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the inhibition of oxidative stress is thought to be a strategy to prevent these diseases as well as against aging. Various studies have reported that the sulfated polysaccharides isolated from seaweeds have antioxidant properties [13,14,26,42]. Wang et al (2020) isolated the sulfate polysaccharides (CFPS) from the enzymatic digest of Codium fragile and evaluated the antioxidant activity of CFPS [14].…”
Section: Protective Effect Of Emc Against Aaph-stimulated Oxidative Smentioning
confidence: 99%
“…They also play roles in repairing the damage caused by ROS [ 132 ] which, when induced by oxidative stress, inhibits cell proliferation and causes apoptosis that is also regulated by a complex network of signaling pathways [ 133 ]. Antioxidants protect against oxidative stress damage induced by the regulation of apoptotic-related signaling pathways [ 134 ] ( Table 4 and Figure 2 ).…”
Section: Molecular Mechanism Of Polysaccharide-induced Antioxidantmentioning
confidence: 99%
“…Polysaccharides from Sargassum fulvellum showed dose-dependent potential for scavenging intracellular ROS in 2,2-azobis (2-amidinopropane) hydrochloride (AAPH)-treated monkey kidney fibroblasts (Vero) cells. It inhibited apoptosis by downregulating Bax and caspase-3 and upregulating Bcl-xL and PARP [ 134 ].…”
Section: Molecular Mechanism Of Polysaccharide-induced Antioxidantmentioning
confidence: 99%
“…Ko et al (2016) purified peptides from Olive flounder and investigated their anti-hypertensive activity in in vitro and in vivo models [26]. Wang et al (2019) isolated sulfated polysaccharides from the brown seaweed, Sargassum fulvellum, and evaluated the in vitro and in vivo antioxidant activities of the sulfated polysaccharides [27]. Pang et al (2018) isolated perylenequinone derivatives from marine sponge-derived fungus and investigated the anti-cancer activities of these compounds [28].…”
Section: Introductionmentioning
confidence: 99%